Performance and (post)digital ontologies: A comment from an anthropological point of view - Lalioti, Vasiliki (The Greek Review of Social Research, 2021)
Causey (2016) introduced the concept “postdigital performance” to describe the works of artists who, as he argues, think digitally, that is, they incorporate structural elements of the digital in their performances, in order to resist the systems of control inherent in the contemporary postdigital culture’s networks. Prompted by Causey’s analysis which, within the frame of performance studies, reproduces (dominant western) positivist views on the ontology of the digital (and the humane), in this paper I explore the ways in which the ontological turn in anthropology may shed light on questions concerning the ontology of the digital, without making universalizing claims.